2022
DOI: 10.1155/2022/4974410
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and Mortality Risk of Patients with Sepsis: A Meta-Analysis

Abstract: Background. The association between sarcopenia at admission and mortality in patients with sepsis has not been comprehensively evaluated. We performed a meta-analysis to systematically evaluate the above association. Methods. This meta-analysis included relevant observational studies from Medline, Embase, and Web of Science databases. A random-effect model after incorporation of the intrastudy heterogeneity was selected to pool the results. Subgroup analyses were applied to evaluate the influences of study cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…In this study, the mortality rate of older patients with sepsis was 36.6%, which approximated that reported in a previous study (38.7%) [10]. In consensus with recent meta-analyses [7,8], we found that lower muscle mass, as a continuous variable, was an independent risk factor for 90-day mortality. However, another study showed that muscle wasting-associated comorbidities, rather than sarcopenia, were risk factors for hospital mortality in critically ill patients with abdominal sepsis [16].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, the mortality rate of older patients with sepsis was 36.6%, which approximated that reported in a previous study (38.7%) [10]. In consensus with recent meta-analyses [7,8], we found that lower muscle mass, as a continuous variable, was an independent risk factor for 90-day mortality. However, another study showed that muscle wasting-associated comorbidities, rather than sarcopenia, were risk factors for hospital mortality in critically ill patients with abdominal sepsis [16].…”
Section: Discussionsupporting
confidence: 90%
“…Patients discharged or transferred within 24 hours (n = 40) or without abdominal CT (n = 127) were excluded. CT scans of 16 patients did not meet quality checks, including artifacts (7), muscle or adipose tissue outside the scanned frame (5), and poor differentiation between the muscle and surrounding tissue (4). Therefore, 443 patients were finally included and followed up, with a 90-day mortality rate of 36.6% (162 patients died) (Fig.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, current literature surrounding chronic, post-sepsis illness suggests that much of the disease morbidity occurs in the weeks to months following acute illness [18]. A meta-analysis of 2396 patients investigated sarcopenia as a risk factor for poor post-sepsis outcomes, similarly reported early (in-hospital or 1-month) mortality as the primary measured outcome [19]. This meta-analysis incorporated studies utilizing three different definitions of sepsis, the earliest of which dates back to 1992 [20].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with low skeletal muscle mass are more susceptible to infection and have a higher mortality rate, owing to sepsis, compared with those who have high skeletal muscle mass (7). In recent years, meta-analyses have indicated the impact of skeletal muscle atrophy on sepsis prognosis (8). Cox et al (7) reported that a poor prognosis in sepsis is associated with pre-existing skeletal muscle atrophy rather than acute muscle atrophy due to sepsis alone.…”
Section: Introductionmentioning
confidence: 99%